Fungal Analysis of Aspergillus niger as an Alternative Biosurfactant for Microbial Injection-Enhanced Oil Recovery - Novia Rita; Agus Dahlia; Hanna Soraya; Ilmiati Ilmiati (Testing Center for Oil and Gas LEMIGAS, 2025)
This study aims to evaluate the ability of Aspergillus niger to produce biosurfactants as a cost-effective and environmentally friendly alternative for the microbial-enhanced oil recovery (MEOR) process. Biosurfactants were produced using different carbon sources: waste cooking oil, liquid paraffin, and tapioca flour in Stone Mineral Salt Solution media. The growth and production of biosurfactants from these sources were analyzed through oil displacement tests, emulsification activity, and surface tension measurements. Tapioca flour emerged as the best carbon source, achieving the highest oil displacement area of 6 cm and an emulsification index of 51.3%. These findings suggest that biosurfactants obtained from Aspergillus niger have significant potential for MEOR applications, providing an eco-friendly solution for enhanced oil recovery.